E-PROINFO AND CONTINUING TRAINING FOR TEACHERS IN THE CONTEXT OF THE MUNICIPALITY OF PORTO VELHO - Blackman, Cledenice [UNESP]; Viana, Gizele de Melo (Fundacao Univ Tocantins, 2020)
This article has as main objective to present some characteristics of Public Policies focused on the educational context in the Brazilian territory, more specifically, in the city of Porto Velho, as object of analysis the Programa Nacional de Informatica na Educacao - PROINFO. However, we will conceptualize some terms related to PROINFO which are: continuing education for teachers of basic education, highlighting the main objective of PROINFO, as the municipality of Porto Velho developed this Public Policy in the educational context through the use of the E-PROINFO network during the years 2005/2012. We use the bibliographic methodology based on books, periodicals, specialized magazines and databases, as well as on official publications, as well as,at national, local and oral level by municipal authorities registered at a regional event. Therefore, it was possible to verify that the continuous training for teachers in the Municipality of Porto Velho did not meet some requirements of the principles of Public Management of Excellence, regarding the efficiency in relation to the total number of teachers who successfully participated in the PROINFO training that it occurred in a slow and contradictory way. In the perspective of transparency,media were used to publicize the program's results,respecting, in a certain way, publicity and legality.
Keywords: Continuing Education; Teachers; PROINFO; Porto Velho